Effect of health education intervention on treatment adherence and health status in patients with Chronic obstruction pulmonary disease: A random control trial - Nguyen Thi Thu Trieu; Nguyen Thi Yen Hoai; Nguyen Ngoc Tung; Tran Huu Thong; Nguyen Thi Thu Hien (PLoS ONE, 2025)
Adherence to treatment is critical to effective management of COPD and is key to addressing the growing burden of disease. So, this study conducted to evaluate the effectiveness of a health education intervention on treatment adherence behavior of COPD outpatients and identify the level of health status improvement. A random control trial was conducted in 2022 at two respiratory outpatient clinics in Da Nang City, Vietnam. 90 participants were divided into two group, 45 members of the health education group who received 5-times consulting about disease knowledge, training using inhallers, breathing exercises at clinic, then 12-times teleconsultation; and 45 controls who only joined surveys. Treatment adherence and level of health status improvement were assessed as outcomes. At beginning, there was no significant difference between the intervention and control groups regarding compliance, disease severity, and airway obstruction (p > 0.05). After three months of intervention, adherence to inhaled medication in the intervention group was 3.2 times higher than in the control group, with statistical significance (p = 0.002, OR=3.2; 95% CI: 1.8–5.3). Similarly, adherence to breathing exercises was 2.5 times greater in the intervention group compared to the control group, with a statistically significant result (p = 0.000, OR=2.5; 95% CI: 1.8–3.4). Overall adherence to treatment was 2.2 times higher in the intervention group than in the control group, also showing statistical significance (p = 0.001, OR=2.2; 95% CI: 1.7–3.1). Additionally, the intervention group demonstrated significant improvements in disease severity and airway obstruction (p < 0.001). Education interventions showed effectiveness in increasing treatment adherence and health status of COPD outpatients. Therefore, a broader program should be conducted in the future.